A cohort study of influences, health outcomes and costs of patients' health-seeking behaviour for minor ailments from primary and emergency care settings. Issue 2 (18th February 2015) - Watson, M C; Ferguson, J; Barton, G R; Maskrey, V; Blyth, A; Paudyal, V; Bond, C M; Holland, R; Porteous, T; Sach, T H; Wright, D; Fielding, S
Abstract : Objectives: To compare health-related and cost-related outcomes of consultations for symptoms suggestive of minor ailments in emergency departments (EDs), general practices and community pharmacies. Design: Observational study; prospective cohort design. Setting: EDs (n=2), general practices (n=6) and community pharmacies (n=10) in a mix of rural/urban and deprived/affluent areas across North East Scotland and East Anglia. Participants Adults (≥18 years) presenting between 09:00 and 18:00 (Monday–Friday) in general practices and 09:00–18:00 (Monday–Saturday) in pharmacies and EDs with ≥1 of the following: musculoskeletal pain; eye discomfort; gastrointestinal disturbance; or upper respiratory tract-related symptoms. Interventions: Participants completed three questionnaires: baseline (prior to index consultation); satisfaction with index consultation and follow-up (2 weeks after index consultation). Main outcome measures: Symptom resolution, quality of life, costs, satisfaction and influences on care-seeking behaviour. Results: 377 patients participated, recruited from EDs (81), general practices (162) and community pharmacies (134). The 2-week response rate was 70% (264/377). Symptom resolution was similar across all three settings: ED (37.3%), general practice (35.7%) and pharmacy (44.3%). Mean overall costs per consultation were significantly lower for pharmacy (£29.30 (95% CI £21.60 to £37.00)) compared with general practice (£82.34 (95% CI £63.10 to £101.58)) and ED (£147.09 (95% CI £125.32 to £168.85)). Satisfaction varied across settings and by measure used. Compared with pharmacy and general practice use, ED use was significantly (p<0.001) associated with first episode and short duration of symptom(s), as well as higher levels of perceived seriousness and urgency for seeking care. Convenience of location was the most common reason for choice of consultation setting. Conclusions: These results suggest similar health-related outcomes and substantially lower costs with pharmacy consultations for minor ailments. Effective strategies are now needed to shift demand for minor ailment management away from EDs and general practices to the community pharmacy setting.